The effect of hybridisation on mechanical properties and water absorption behaviour of woven jute/ramie reinforced epoxy composites - Tezara, Cionita; Hadi, Agung Efriyo; Siregar, Januar Parlaungan; Muhamad, Zalinawati; Mohamad Hamdan, Mohammad Hazim; Oumer, Ahmed Nurye; Jaafar, Jamiluddin; Irawan, Agustinus Purna; Teuku Rihayat, Teuku Rihayat; Fitriyana, Deni Fajar (MDPI, 2021)
: Recently, the most critical issue related to the use of natural fibre-reinforced polymer composites (NFRPC) is the degradation properties of composites exposed to the environment. NFRPC’s moisture absorption behaviour has adverse effects on the composite’s mechanical properties and dimensional stability. The purpose of this study is to analyse the mechanical properties of epoxy composites reinforced by jute–ramie hybridisation. This study also analysed the effect of stacking sequence hybridisation of the jute–ramie composite on water absorption behaviour. A five-layer different type of stacking sequence of single and hybrid jute–ramie is produced with the hand lay-up method. The results obtained from this study found that the mechanical properties and water absorption behaviour of a single jute fibre are lower compared to a single ramie fibre. The hybrid of jute–ramie has been able to increase the performance of composite compared to pure jute composites. The mechanical properties of the hybrid jute–ramie composite show a reduction effect after exposure to an aqueous environment due to the breakdown of fibre matrix interfacial bonding. However, after 28 days of immersion, all types of the stacking sequence’s mechanical properties are still higher than that of pure epoxy resin. In conclusion, the appropriate sequence of stacking and selecting the material used are two factors that predominantly affect the mechanical properties and water absorption behaviour. The hybrid composites with the desired and preferable properties can be manufactured using a hand-lay-up technique and used in the various industrial applications.